Supreme Thinking: Christianity & the Limitations of Artificial Intelligence. - Fowler, Thomas B. (Touchstone: A Journal of Mere Christianity)
The article examines the relationship between artificial intelligence (AI) and human understanding, arguing that AI's limitations reveal the superiority of the Judeo-Christian view of humanity. It critiques the assumption that AI operates similarly to human intelligence, highlighting the failure of AI systems, particularly generative AI like chatbots, to fully replicate human creativity and perception of reality.